MAKNA TEOLOGI HINDU DALAM TRADISI TAMPIOG DI DESA PAKRAMAN MANUKAYA LET, KECAMATAN TAMPAKSIRING, KABUPATEN GIANYAR - Ni Wayan Yas Ronajoti (Pangkaja: Jurnal Agama Hindu, 2022)
Hindus in Bali cannot be separated from beliefs and traditions that are considered to have religious and ethical values. Tradition in Hindu society in Bali has many forms, all of which become the breath in the implementation of religious ceremonies carried out through the Panca Yadnya. One of them is the Tampiog Tradition in the village of Pakraman Manukaya Let which is held in a series of piodalan at Bale Agung Temple. The Tampiog tradition is the tradition of kicking a mound of embers. This tradition has been accepted from generation to generation by the people of Pakraman Manukaya Let Village. The Tampiog tradition is a symbol of harmony between Bhuana Agung and Bhuana Alit. This paper describes how the form of implementation and Hindu theology in the Tampiog Tradition in Pakraman Manukaya Let Village, Tampaksiring District, Gianyar Regency. The technique used by the author in collecting data is observation technique. The Tampiog tradition contains many theological meanings of Hinduism which is very important for the development of Hindu rituals. This is what motivated the author to conduct research.